A carbon dot doped lanthanide coordination polymer nanocomposite as the ratiometric fluorescent probe for the sensitive detection of alkaline phosphatase activity. Issue 9 (23rd April 2021) - Sun, Weidi; Han, Xue; Qu, Fengli; Kong, Rong-Mei; Zhao, Zilong
Abstract : Based on the stimulus-responsive lanthanide coordination polymer and the stable fluorescence of carbon dots (CDs), a simple ratiometric fluorescence sensing strategy was proposed to detect ALP activity. Abstract : The development of sensitive methods for alkaline phosphatase (ALP) activity analysis is an important analytical topic. Based on the stimulus-responsive lanthanide coordination polymer, a simple ratiometric fluorescence sensing strategy was proposed to detect ALP activity. A carbon dot (CD) doped fluorescent supramolecular lanthanide coordination polymer (CDs@Tb-GMP) was prepared with Tb 3+ and the ligand guanine single nucleotide (GMP). To construct a ratiometric fluorescence biosensor, the fluorescence of Tb-GMP was used as a response signal, and the fluorescence of CDs was used as a reference signal due to its good stability. When excited at 290 nm, the polymer network Tb-GMP emits characteristic fluorescence at 545 nm, while the CDs encapsulated in the polymer network emit fluorescence at 370 nm. After adding ALP to the system, the substrate GMP can be hydrolyzed by ALP, resulting in the destruction of the polymer network. Accordingly, the fluorescence of Tb-GMP significantly decreased, while the fluorescence of CDs slightly increased due to their release from the polymer network. By comparing the relationship between the fluorescence intensity ratio of the two signals and the concentration of ALP, sensitive detection of ALP could be achieved with the linear range from 0.5 to 80 U L −1 and a detection limit of 0.13 U L −1 . Furthermore, the proposed ratiometric sensing system was applied to the detection of ALP in human serum samples with desirable results, indicating potential application in clinical diagnosis.